Peran Kepala Tata Usaha Dalam Meningkatkan Efisiensi Administrasi Sekolah Di Madrasah Aliyah Laboratorium Uinsu Medan - Azhari Panjaitan; Muhammad Rifa’i (Jurnal Ragam Pengabdian, 2026)
This study aims to describe and analyze the role of the Head of Administration (KTU) in improving school administrative efficiency at the Madrasah Aliyah Laboratorium, UIN Sumatera Utara Medan. This study used a qualitative approach, with data collection techniques through interviews, observations, and documentation studies. The primary data were obtained from an interview with Misbah Lubis, S.Pd.I, Head of Administration at the MAS Laboratorium, UIN SU Medan. The results indicate that the KTU plays a strategic role in planning, organizing, implementing, implementing digital innovation, and evaluating school administration. Administrative efficiency is achieved through thorough planning, effective coordination, and the application of information technology in data management and administrative services. These findings confirm that the KTU makes a significant contribution to improving the effectiveness of school management and the quality of madrasah educational services.